Association of dental caries experience with individual and contextual variables in Brazilian children - Brizon, Valeria Silva Cândido; Rojas, Gabriela Christiel Soto; Ambrosano, Glaucia Maria Bovi; Guerra, Luciane Miranda; Pereira, Antonio Carlos (European Journal of General Dentistry, 2016)
Context: There is a trend toward reduction in the caries index in populations of schoolchildren in developed and developing countries. In spite of this reduction, 53.4% Brazilian children present caries experience in primary dentition. Aims: To evaluate the association between dental caries experience in 5-year-old Brazilian and individual and contextual variables. Settings and Design: An analytical cross-sectional study was conducted. Materials and Methods: Data of a national oral health epidemiological survey - SB Brazil 2010 were taken. The outcome studied was caries experience measured by the decayed, missing, and filled teeth (dmft) index. The independent variables were classified into individual (sex, occlusion, treatment need, number of persons′ resident in the home, number of bedrooms in the residence, number of goods/assets, and family income) and contextual (family financial aid grand, national health system performance index (Índice de Desempenho do Sistema Único de Saúde [IDSUS]), Gross National Product, per capita, Human Development Index, and fluoridated water) variables. Statistical Analysis Used: The data were initially analyzed by the Chi-square test, then was applied the multilevel model. Results: Only the contextual variable that evaluates access and quality of public services (IDSUS) was observed to affect the children′s dmft index. The individual variables: male sex (P = 0.0005), occlusion (P = 0.0437), dental treatment need (P < 0.0001), number of persons′ resident in the home (P < 0.0001), number of bedrooms in the residence (P = 0.0152), number of goods/assets (P = 0.0147), and family income (P = 0.0044) were significant. Conclusions: There is an impact of social determinants on health at individual level but only the IDSUS contextual variable was associated with dmft. Are necessary development public policies to deal with caries with a focus on these determinants?
Keywords: Brazil; dental caries; dental health surveys; multilevel analysis; oral health